Website-Based Academic Service Development with ADDIE Design in Higher Education - Taqwa Taqwa; Sumardin Raupu (STAI Hubbulwathan Duri, 2022)
This study aims to develop a website-based academic service at the Islamic Educational Management Study Program at an Islamic university in Palopo. Research and development (RD) using ADDIE Design was employed to develop the website. The data collection technique used was an observation, interviews with five students, the distribution of questionnaires, and documentation, among other methods. The data analysis technique was carried out qualitatively and quantitatively through data analysis techniques of validity, practicality, and effectiveness. At the Islamic Educational Management Study Program, an Islamic university in Palopo, this research results in the development of website-based academic services, which students can use to obtain educational services with a high level of validity from the layout/design, the material/website, and the language in the product in the very valid category, according to the findings. Regarding the practicality and effectiveness of the website-based academic services developed for use, they fall into